Strategi Kerjasama Pengembangan Institusi Halal: Implementasi pada Halal Center - Poppy Arsil; Rumpoko Wicaksono; Hety Handayani Hidayat; Dian Novitasari (ITB AAS INDONESIA Surakarta, 2022)
The halal industry has the potential to grow, supported by a gradual implementation of a mandatory halal regulation according to Law No 33 the year 2014 regarding Halal Product Guarantee. To support this program, Halal Product Guarantee Agency (BPJPH) has encouraged universities to establish Halal Centers since 2019. The goal of this study is to investigate the Halal Center's collaboration strategy with other agencies supporting halal mandatory programs using the Analytical Hierarchy Process approach. This research interviewed 40 food and beverage business owners and experts in 2021. Data analysis is divided into three stages: decomposition, pairwise comparisons, and priority synthesis. The hierarchical structure is comprised of four levels, namely the variables affecting collaboration, the actors involved, the goals, and the cooperation strategy. The results show that capital (0.617) and institutional policy (0.30) affect the growth of Halal Center cooperation. While BPJPH (0.33), the government (0.31), and private institutions (0.12) all contribute to the development of the halal center collaboration. The purpose of developing the halal center collaboration is to help accelerate MSME to obtain halal certification (0.67). While the Cooperation strategy suggests that the use of government assistance funds (0.46), as well as collaboration with private institutions (weight 0.34).